2008
DOI: 10.4314/thrb.v10i1.14342
|View full text |Cite
|
Sign up to set email alerts
|

Repellency property of long chain aliphatic methyl ketones against <i>Anopheles gambiae</i> s.s

Abstract: Long chain aliphatic methyl ketone series of C 7 -C 15 were tested for repellency activity against the malaria transmitting mosquito Anopheles gambiae s.s. All methyl ketones produced a dose dependent (P<0.001) repellency response with 2-tridecanone giving comparable protection efficacy to DEET at 10% and 1% concentrations. Aliphatic methyl ketones of C 7 -C 10 had lower activity than those of C 11 -C 15. However, within this range compounds with odd carbon atoms (2-undecanone, 2-tridecanone and 2-pentadecanon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…Amongst the compounds isolated in F. thonningii essential oils is the C-15 compound; 6, 10, 14 trimethyl-2-pentadecanone an aliphatic methyl ketone which has been reported to possess insect repellent properties. The repellent properties of 6, 10, 14 trimethyl-2-pentadecanone at a concentration of 10 % (w/v), were comparable to those of the commercial repellent, N, N diethyl-m-toluamide (DEET) (Innocent, 2008).…”
Section: Antiprotozoal Propertiesmentioning
confidence: 80%
See 1 more Smart Citation
“…Amongst the compounds isolated in F. thonningii essential oils is the C-15 compound; 6, 10, 14 trimethyl-2-pentadecanone an aliphatic methyl ketone which has been reported to possess insect repellent properties. The repellent properties of 6, 10, 14 trimethyl-2-pentadecanone at a concentration of 10 % (w/v), were comparable to those of the commercial repellent, N, N diethyl-m-toluamide (DEET) (Innocent, 2008).…”
Section: Antiprotozoal Propertiesmentioning
confidence: 80%
“…A study carried out to evaluate the antiplasmodial activity of F. thonningii against Plasmodium falciparum the protozoan parasite that causes malaria reported no significant antiplasmodial activity (Jansen et al, 2010). F. thonningii possibly just possesses good insect repellent properties and hence reduces the contact of the vector with humans, minimising incidence of malaria transmission (Jansen et al, 2010;Innocent, 2008). Amongst the compounds isolated in F. thonningii essential oils is the C-15 compound; 6, 10, 14 trimethyl-2-pentadecanone an aliphatic methyl ketone which has been reported to possess insect repellent properties.…”
Section: Antiprotozoal Propertiesmentioning
confidence: 99%
“…Studies showed that the compound was more persistent than the EPA-registered active ingredient in BioUD , 2-undecanone, in laboratory choice bioassays on filter paper against two species of ticks. Innocent et al (2008) also found 2-tridecanone to be more effective than 2-undecanone as a mosquito repellent. In the current study, 2-tridecanone was a persistent repellent on cotton cloth.…”
Section: Discussionmentioning
confidence: 91%
“…More recently, unformulated 2-tridecanone was found to be a more effective repellent than 2-undecanone against mosquitoes (Innocent et al, 2008). Similar comparative studies have not been conducted with ticks, and no published studies on the tick repellency of 2-tridecanone are currently available.…”
Section: Introductionmentioning
confidence: 96%
“…Hexahydroxyfarnesylacetone (6,10,14-trimethyl-2-pentadecanone) may repel insects, while according to some studies aliphatic methyl ketones with long chains exert such activity (Innocent et al 2008). Also, identified aliphatic alcohols including 2-nonen-1-ol, 2-tetradecen-1-ol, 7-tetradecen-1-ol, and 2-hexyl-1-decanol are common components of essential oils extracted from different plants and for which antimicrobial activity was demonstrated (Manilal et al 2009;Ü çüncü et al 2010;Ogunlesi et al 2010;Rahmat et al 2006).…”
Section: Resultsmentioning
confidence: 99%